Portugal e as irmandades da fala - Beramendi, Justo (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2017)
In the development of the ideology of Galician nationalism Portugal works as a defective subject of national reintegration, as necessary complement to ideal nation-building of Galice in ethno-historical clef. This causes cultural relations between Galician and Portuguese intellectuals during the Twenties and Thirties, but barely political relations and never generate the demand for the political union of the two countries.